The Warm-up and Closure Pattern Utilized by Islamic Education Teachers of the Basic Stage in Karak Governorate - Khazer, Mohannad (Jordan Journal of Educational Sciences, 2005)
This research aimed at defining patterns of warm-up and closure used by Islamic education teachers through their teaching, in the basic stage at Al-KARAK city in Jordan. The research sample included (98) male teachers at Al-KARAK and Al-MAZAR directorates. The research instrument was an observation consisting of (18) items. Findings showed an ignorance by the teachers of the appliance of both warm-up and closure. The number of lessons which included both of them was ( 58) lessons, and a percentage of (30%). In addition, the findings showed a clear decrease of the percentage of teachers use of different patterns of warm-up and closure. The most frequent warm-up pattern observed was linking the present lesson with the previous one, and the most frequent closure pattern was acknowledging students with the title of next lesson. In the light of the mentioned findings, a number of recommendations were stated (Key Words: Warm-up Patterns, Closure Patterns, Islamic Education Teacher, Basic Stage